Osteoarthritis development related to cartilage quality-the prognostic value of dGEMRIC after anterior cruciate ligament injury. Issue 11 (November 2019) - Tjörnstrand, J.; Neuman, P.; Svensson, J.; Lundin, B.; Dahlberg, L.E.; Tiderius, C.J.
Summary: Objective: Rupture of the anterior cruciate ligament (ACL) increases the risk of developing osteoarthritis (OA). Delayed Gadolinium enhanced magnetic resonance imaging (MRI) of cartilage (dGEMRIC) investigates cartilage integrity through T1-analysis after intravenous contrast injection. A high dGEMRIC index represents good cartilage quality. The main purpose of this prospective cohort study was to investigate the prognostic value of the dGEMRIC index regarding future knee OA. Method: 31 patients with ACL injury (mean age 27 ± 6.7 (±SD) years, 19 males) were examined after 2 years with 1.5T dGEMRIC of femoral cartilage. Re-examination 14 years post-injury included weight-bearing knee radiographs, Lysholm and Knee Osteoarthritis Outcome Score (KOOS). Results: At the 14-year follow up radiographic OA (ROA) was present in 68% and OA symptoms (SOA) in 42% of the injured knees. The dGEMRIC index of the medial compartment was lower in knees that developed medial ROA, 325 ± 68 (ms±SD) vs 376 ± 47 (51 (7–94)) (difference of means (95% confidence interval (CI))), in patients that developed symptomatic OA (SOA), 327 ± 61 vs 399 ± 42 (52 (11–93)), and poor knee function 337 ± 54 vs 381 ± 52 (48 (7–89)) compared to those that did not develop ROA, SOA or poor function. The dGEMRIC index correlated negatively with the OARSI osteophyte score in medial ( r = −0.44, P = 0.01) and lateral ( r = −0.38, P = 0.03) compartments. Conclusion: The associations between a low dGEMRIC index and future ROA, as well as SOA, are in agreement with previous studies and indicate that dGEMRIC has a prognostic value for future knee OA.